Neuroendocrine responses to running in women after zinc and vitamin E supplementation - Singh, A.; Papanicolaou, D. A.; Lawrence, L. L.; Howell, E. A; Chrousos, G. P.; Deuster, P. A. (Medicine & Science in Sports & Exercise, 1999)
Acute supplementation with zinc or vitamin E did not influence the effects of exhaustive running on metabolic and endocrine responses in women. The effects of chronic supplementation on neuroendocrine responses to exercise remain to be determined.